Formación en revisión sistemática como modalidad de TFG: El talón de Aquiles de nuestros estudiantes - Solís, Patricia; Arroyo Resino, Delia; Camilli Trujillo, Celia (Bordon. Revista de Pedagogia, 2023)
INTRODUCTION. Various changes are being originated from the European Higher Education Area and the Bologna Declaration of Spanish universities, among them, we highlight the obli-gation for students to carry out a Final Degree Project (FDP). Starting from the importance of this work and focusing on the modality of systematic reviews, this research analyzes the effect of a training program in that modality on the knowledge of the students, who are going to carry out a final project, using the systematic review. METHOD. A mixed concurrent triangulation design is used: a quasi-experimental design with pre-test and post-test without a control group in a case study. The sample for the quantitative analysis was selected by accessibility, with a total of 73 students, of which 14 participated randomly and voluntarily in conducting an inter-view. In this way, as instruments for collecting information, we use a questionnaire, made up of 24 items on a 5-point Likert scale response, and a structured interview to complete the information obtained in the questionnaires. RESULTS. Significant differences were found in all the items between the pre and post scores, the latter being higher, with very large effect sizes. Likewise, the discourse analysis showed the parallelism with the quantitative results and the satisfaction of the students after the training received. DISCUSSION. This research highlights the impact that this type of training has on our students, being the same effective for students to acquire the basic skills that allow them to carry out systematic reviews in the completion of the FDP. Therefore, the need for universities to offer this type of training as part of the teach-ing-learning process is highlighted.
Training in systematic review as a modality of the Final Degree Project: The Achilles Heel of our students
Keywords: final degree project; formative research; literature reviews; research skills; systematic review; undergraduate students; Scopus